Nutrition vs Malnutrition in Prenatal Period for Pregnant and Fetus Care - Dr.ibtihal ALhamad; Dr.Amjad ALbanny; Dr.Ahmad ALnahwai; Dr.Hussain ALmuhanna; Fadhel BoKheder; Ibrahim ALshuwaysh; Aqeen ALmutlaq; Manal ALquraishi; Huda ALayesh; Awatif ALali; Afrah ALsaihati; Shefa ALsabah; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The importance of nutrition in pregnancy cannot be overstated. It maintains maternal energy requirements, provides substrate for the development of new fetal tissues, and builds energy reserves for postpartum lactation. Recommendations for prenatal nutrition typically focus on weight gain and dietary intake in pregnancy.The metabolic demands of pregnancy require supplemental dietary intake. Additional energy (caloric) intake is required to support recommended weight gain. Because energy requirements in pregnancy are increased by 17% over the nonpregnant state, a woman of normal weight should consume an additional 300 kcal/d. This energy should be of high nutrient density. Nutrient density reflects the amount of protein, vitamins, and minerals per 100 kcal of food.